Information systems architecture and technology : proceedigs of 40th anniversary International Conference on Information Systems Architecture and Technology - ISAT 2019.: proceedigs of 40th anniversary International Conference on Information Systems Architecture and Technology - ISAT 2019. Part 3 (2019) - Unknown
No abstract available